2022
DOI: 10.2514/1.j059696
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analyses of Fluidic Thrust Vector Control System Using Dual Throat Nozzle

Abstract: to initiate your request. See also AIAA Rights and Permissions www.aiaa.org/randp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The study found that the arc-shaped BDTN not only achie high thrust efficiency and thrust coefficient but also significantly reduced total pres loss compared to BDTN with a V-shaped bypass channel. In additional, Maruyama et al [81] employed a direct simulation Monte C method to conduct a numerical analysis of the flow within a rocket motor nozzle. T investigation revealed that a steady thrust deflection of approximately 18° was achie when the secondary jet's mass flow rate accounted for 5% of the total fluid.…”
Section: Thrust Vectoringmentioning
confidence: 99%
See 1 more Smart Citation
“…The study found that the arc-shaped BDTN not only achie high thrust efficiency and thrust coefficient but also significantly reduced total pres loss compared to BDTN with a V-shaped bypass channel. In additional, Maruyama et al [81] employed a direct simulation Monte C method to conduct a numerical analysis of the flow within a rocket motor nozzle. T investigation revealed that a steady thrust deflection of approximately 18° was achie when the secondary jet's mass flow rate accounted for 5% of the total fluid.…”
Section: Thrust Vectoringmentioning
confidence: 99%
“…To address this issue, they improved the nozzle de and discovered that by widening the second throat to 1.50 times the cross-sectional of the first throat, the unexpected thrust deflection during zero flow of the secondar was effectively suppressed (refer to Figure 17). In additional, Maruyama et al [81] employed a direct simulation Monte Carlo method to conduct a numerical analysis of the flow within a rocket motor nozzle. Their investigation revealed that a steady thrust deflection of approximately 18 • was achieved when the secondary jet's mass flow rate accounted for 5% of the total fluid.…”
Section: Thrust Vectoringmentioning
confidence: 99%
“…The shock vector control (SVC) or thrust vector control (TVC) method involves injecting secondary flow into the divergence section of the nozzle to generate induced shock waves that deflect the primary flow and alter the direction of thrust [13][14][15]. This technique has been implemented in missiles such as the Minuteman 3 ICBM and the Julang 2 ICBM and has undergone significant advancements in recent years [13,[16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The two dominant FTV mechanisms are co-flow [6][7][8] and counter-flow mechanisms [17][18][19], wherein the jet is blown in the same direction as the primary jet in the case of the former. In the latter mechanism, the secondary jet is sucked in against the outgoing primary jet.…”
Section: Introductionmentioning
confidence: 99%
“…The co-flow and its variant have been investigated by a number of researchers in recent times. For instance, Maruyama et al [18] examined the flow characteristics of a two-dimensional dual-throat nozzle (DTN) using numerical analysis. Computational work on flow dynamics behavior in two-dimension DTN using different input functions, such as step and ramp, were carried out by Ferlauto and Marsilio [19].…”
Section: Introductionmentioning
confidence: 99%